Electrophoretic efficiency of an ionic toothbrush - Gaberšček, Miran (Acta chimica slovenica, 2006)
The eventual electrophoretic effects during application of an ionic toothbrushare examined. Firstly, the electrical conditions to which the teeth are exposed during application of the ionic tootbrush are determined. Secondly, a method for monitoring the change of bacteria number density on thesurface of extracted teeth under the influence of external electric field is presented. After a regular application of the ionic toothbrush this change is detectable, but - from the practical point - negligibly small. The study does not preclude other possible effects of the ionic toothbrush (e.g. electrolysis on teeth surface).
Keywords: bacteria; bakterije; elektroforeza; ionske zobne ščetke